Quantitative magnetic resonance imaging and neuropsychological functions in dementia of the Alzheimer type - Pantel, Johannes; Schröder, Johannes; Schad, Lothar R.; Friedlinger, Michael; Knopp, Michael V.; Schmitt, R.; Geissler, M.; Blüml, S.; Essig, Marco; Sauer, H. (Psychological medicine, 1997)
Background. The aim of the present study was to investigate neuropsychological functions in - dementia of the Alzheimer type (DAT) with respect to morphological changes that were revealed - by quantitative magnetic resonance imaging (MRI).Methods. Twenty patients with DAT (NINCDS-ADRDA criteria) and 10 healthy age and sex - matched controls were included. The neuropsychological function was evaluated on a test - battery covering the severity of dementia, verbal and visual memory, concentration and - attention, language skills and general intelligence as well as activities of daily living. 3D MRI - sequences were acquired using a 1.5 T Siemens MAGNETOM. Whole brain volume, total - intracranial volume (TIV), volume of the frontal and temporal lobes and volumes of the - amygdalahippocampus complex (AHC) were assessed using the newly developed software NMRWin.Results. Apart from TIV all morphometric parameters differed significantly between the - diagnostic groups. AHC volumes discriminated best between the groups, with only a small overlap. - AHC atrophy exceeded generalized atrophy. These findings were confirmed when the data were - reanalysed after dividing the DAT patients into a mildly and moderately affected group. The - severity of dementia was significantly correlated with the volumes of the AHC and the volumes - of the temporal lobes bilaterally, but not with the whole brain volume and the volumes of the - frontal lobes.Conclusions. These results underline the important role of the temporal substructures for - aetiology and progression of DAT. They indicate that the volume of the AHC can be - monitored by MRI and may be used to follow up the disease process.
Gesehen am 10.11.2021